Controversies in the Anesthetic Management of Intraoperative Rupture of Intracranial Aneurysm - Tumul Chowdhury; Andrea Petropolis; Marshall Wilkinson; Bernhard Schaller; Nora Sandu; Ronald B. Cappellani (Anesthesiology Research and Practice)
Despite great advancements in the management of aneurysmal subarachnoid hemorrhage (SAH), outcomes following SAH rupture have remained relatively unchanged. In addition, little data exists to guide the anesthetic management of intraoperative aneurysm rupture (IAR), though intraoperative management may have a significant effect on overall neurological outcomes. This review highlights the various controversies related to different anesthetic management related to aneurysm rupture. The first controversy relates to management of preexisting factors that affect risk of IAR. The second controversy relates to diagnostic techniques, particularly neurophysiological monitoring. The third controversy pertains to hemodynamic goals. The neuroprotective effects of various factors, including hypothermia, various anesthetic/pharmacologic agents, and burst suppression, remain poorly understood and have yet to be further elucidated. Different management strategies for IAR during aneurysmal clipping versus coiling also need further attention.